Identification of compendial nonionic detergents for the replacement of Triton X‐100 in bioprocessing. (22nd January 2022) - Hunter, Alan K.; Rezvani, Kamiyar; Aspelund, Matthew T.; Xi, Guoling; Gadre, Dhanesh; Linke, Thomas; Cai, Kang; Mulagapati, Sri Hari Raju; Witkos, Tomasz
Abstract: We have systematically investigated six compendial nonionic detergents as potential replacements for Triton ×‐100 in bioprocessing applications. Use of compendial raw materials in cGMP bioprocessing is advantageous for a variety of reasons including material specifications developed to meet stringent pharmaceutical product quality requirements, regulatory familiarity and comfort, and availability from vendors experienced supplying the biopharmaceutical industry. We first examine material properties of the detergents themselves including melting point and viscosity. Process performance and product contact in real‐world bioprocess applications are then investigated. Lastly, we test the detergents in virus inactivation (VI) experiments with recombinant proteins and adeno‐associated virus. Two of the detergents tested, PEG 9 Lauryl Ether and PEG 6 Caprylic/Capric Glycerides, showed favorable properties that make them attractive for use as potential Triton X‐100 replacements. Process performance testing indicated negligible impact of the detergents on product yield, purity, and activity compared to a control with no detergent. Importantly, both PEG 9 Lauryl Ether and PEG 6 Caprylic/Capric Glycerides demonstrated very fast VI kinetics with complete inactivation of XMuLV observed in less than 1 min at a target 1% detergent concentration. Potential advantages and disadvantages of both candidate detergents for use in cGMP bioprocessing are summarized and discussed.